Ownership, institutions, and capital structure: Evidence from China - LI, Kai (Institutional Knowledge at Singapore Management University, 2009)
We employ a unique data set to explore the role of ownership structure and institutional development in debt financing of non-publicly traded Chinese firms. We show that state ownership is positively associated with leverage and firms’ access to long-term debt, while foreign ownership is negatively associated with all measures of leverage. Surprisingly, firms in better developed regions are associated with reduced access to long-term debt, suggesting the availability of alternative financing channels and the tightening of the lending standards under the on-going banking reform. The combination of ownership structures and institutions explains up to 6% of the total variation in firms’ leverage decisions, while firm characteristics alone explain no more than 8% of the variation. Further, we show that non-state-owned firms tend to have lower total and short-term debt than their state-owned counterparts in less developed regions. Finally, we show that state-owned firms’ easy access to long-term debt is positively associated with long-term investment and negatively associated with firm performance.